0 like 0 dislike
Solve using the quadratic formula. 9q2 + 6q + 1 = 0 Write your answers as integers, proper or improper fractions in simplest form, or decimals rounded to the nearest hundredth. q = or q =
by

1 Answer

0 like 0 dislike
The solution to the quadratic equation is given as follows: [tex]q = -\frac{1}{3}[/tex]

What is a quadratic function?

A quadratic function is given according to the following rule:

[tex]y = ax^2 + bx + c[/tex]

The solutions are:

- [tex]x_1 = \frac{-b + \sqrt{\Delta}}{2a}[/tex]

- [tex]x_2 = \frac{-b - \sqrt{\Delta}}{2a}[/tex]

In which:

[tex]\Delta = b^2 - 4ac[/tex]

In this problem, the equation is:

9q² + 6q + 1.

The coefficients are a = 9,b = 6, c = 1, hence:

[tex]\Delta = 6^2 - 4(9)(1) = 0[/tex]

[tex]q_1 = \frac{-6 + \sqrt{0}}{2(9)} = -\frac{1}{3}[/tex]

[tex]q_2 = \frac{-6 - \sqrt{0}}{2(9)} = -\frac{1}{3}[/tex]

More can be learned about quadratic functions at  

by
Welcome to AskTheTask.com, where understudies, educators and math devotees can ask and respond to any number related inquiry. Find support and replies to any numerical statement including variable based math, geometry, calculation, analytics, geometry, divisions, settling articulation, improving on articulations from there, the sky is the limit. Find solutions to numerical problems. Help is consistently 100 percent free!

Questions

No related questions found